Instytucja nocnego burmistrza. Analiza prawna na tle uchwały Rady Miasta Krakowa - Wyszyński, Filip (Wydawnictwo Naukowe UAM, 2021)
Celem niniejszego opracowania jest analiza instytucji nocnego burmistrza. Instytucja ta została wprowadzona w kilkudziesięciu miastach rozlokowanych na całym świecie. Kraków był pierwszym miastem w Polsce, gdzie w 2019 r. próbowano wprowadzić instytucję nocnego burmistrza. Uchwała była jednak dotknięta nieważnością z punktu widzenia formalnego. W opracowaniu rozważono pozycję prawną nocnego burmistrza w ujęciu prawnoporównawczym.

The purpose of this study is to analyze the institution of the night mayor. This institution was introduced in several dozens of cities around the world. Kraków was the first city in Poland where an attempt to implement the institution of the night mayor was made, and the attempt took place in 2019. However, the resolution was invalid from a formal point of view. The study considers the legal position of the night mayor from a comparative legal perspective.
Institution of the night mayor. Comparative legal analysis in light of the resolution of the Kraków City Council
Keywords: nocny burmistrz; definicja prawna nocy; gospodarka nocna; night mayor; legal definition of night; night-time economy